The Knowledge And Practices Of Natural Treatments As Self-Care Measures For Postpartum Women To Prevent Postpartum Complications - Shinta Ayu Nani (International Journal of Health Engineering and Technology, 2026)
The postpartum period is a crucial phase following childbirth, characterized by the mother’s physical, psychological, and social recovery. During this period, efforts to prevent postpartum complications require appropriate care, including natural treatment practices that are still widely used today as a form of self-care. The implementation of these practices is influenced by various factors, such as cultural values, personal experience, and the social environment surrounding the mother’s life. This study aims to explore the knowledge and practices of natural treatments among postpartum mothers in the community and to examine their role in preventing postpartum complications. This study employed a qualitative approach with a phenomenological design. A total of 22 postpartum mothers were selected as participants through purposive sampling from three Community Health Centers providing Basic Obstetric and Neonatal Emergency Services (PONED) in Kendal Regency. Data collection was conducted through interviews using a guide prepared by the researcher. All information was recorded in field notes, then transcribed verbatim and analyzed using thematic analysis to identify the main themes of the study. The analysis yielded six themes, including mothers’ knowledge of natural treatments, the sources of information that shaped that knowledge, the practices they employed, their reasons for choosing those practices, the perceived benefits and risks, and the influence of family, culture, and health care providers on the decision-making process. The most common forms of natural treatment include consuming traditional herbal remedies and herbs, oxytocin massage, lactation massage, warm compresses, and the use of pilis, param, tapel, and bengkung. This study concludes that the practice of natural treatments among postpartum mothers is a form of self-care behavior shaped by the interplay of knowledge, experience, culture, and social support. Therefore, the development of maternal health education must integrate culturally sensitive approaches with scientific evidence so that safe natural treatments can be optimally implemented as part of efforts to prevent postpartum complications.